SISTEM PAKAR DIAGNOSA VIRUS KOMPUTER BERBASIS WEB (Jurnal Dinamika Informatika, 2014)
Computer viruses can damage (eg by corrupting the data on the document), make computer users feel annoyed, or no effect at all. System development methods used in this study is an expert system that consists of the identification, conceptualization, formalization, implementation, evaluation and development system. System design using the Levelled DFD context diagram and consists of a Level 0 DFD and ERD. Creating a website using PHP programming and MySQL database..   Keywords – Expert System, Computer Virus Komputer, PHP, MySQL